2022
DOI: 10.54543/etnik.v1i4.41
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Atraksi, Aksesibilitas, Amenitas dan Kualitas Pelayanan Terhadap Minat Kunjungan Ulang Wisatawan di Pulau Kumala Kabupaten Kutai Kartanegara

Abstract: The tourism industry in Indonesia continues to grow along with the development of technology, transportation, and information. So that companies or tourism business actors must pay attention to tourism marketing by promoting service products and service quality in these tourist destinations. Kumala Island is a leading tourist attraction in Kutai Kartanegara Regency. The purpose of this study was to determine the effect of attractions, accessibility, amenities, and quality of service on the interest in repeat v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…1. 4A (Attraction, Amenity, Accesibility, and Ancillary) Menurut Cooper dalam (Dita & Zaini, 2022) Pada daerah tujuan wisata atau destinasi harus memiliki beberapa komponen yang meliputi atraksi lokal atau daya tarik (attraction), kemudahan akses (acces) karena adanya transportasi lokal dan terminal, ketersediaan berbagai fasilitas seperti akomodasi, restoran, hiburan, belanja dan layanan lainnya (amenity), serta organisasi pariwisata yang diperlukan untuk layanan pariwisata (ancillary). Atraksi merupakan salah satu produk utama destinasi.…”
Section: Hasil Dan Pembahasanunclassified
“…1. 4A (Attraction, Amenity, Accesibility, and Ancillary) Menurut Cooper dalam (Dita & Zaini, 2022) Pada daerah tujuan wisata atau destinasi harus memiliki beberapa komponen yang meliputi atraksi lokal atau daya tarik (attraction), kemudahan akses (acces) karena adanya transportasi lokal dan terminal, ketersediaan berbagai fasilitas seperti akomodasi, restoran, hiburan, belanja dan layanan lainnya (amenity), serta organisasi pariwisata yang diperlukan untuk layanan pariwisata (ancillary). Atraksi merupakan salah satu produk utama destinasi.…”
Section: Hasil Dan Pembahasanunclassified
“…Still, studies found that service quality has a positive and insignificant effect on revisit intention [2].…”
Section: Introductionmentioning
confidence: 99%
“…The tourists having the intention to re-visit are very important because the marketing cost will be less compared to marketing to attract the tourist who comes for the first time. Noting that tourism is a vital source of income, many researchers and practitioners have investigated the factors that direct tourists' intentions to re-visit destinations [1], such as tourist attractions [2], service quality [3], facilities [4], satisfaction [5] [6]. The factor that influences the intention to revisit is customer satisfaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation